A safe space for local knowledge sharing in sustainable tourism: an organisational justice perspective. Issue 4 (3rd April 2023) - Rastegar, Raymond; Ruhanen, Lisa
Abstract: Knowledge is recognised as having more value when it is created and shared amongst stakeholders. Applying knowledge management principles can assist tourism organisations in achieving a competitive advantage. Importantly though, one-way, top-down transfer of knowledge, particularly in developing countries, can result in ignoring valuable local knowledge and compromise sustainable development objectives. Certainly, when considering the context of sustainable tourism, relying solely on more powerful stakeholders' knowledge inputs to make decisions can result in injustice and undermine sustainability values. Given the importance of justice principles to sustainable tourism, this study applies the concept of organisational justice with a focus on the three dimensions of distributive, procedural and interactional justice to examine local knowledge sharing in tourism development. To address issues of justice and fairness in the context of sustainable tourism development, this study proposes a safe space framework to facilitate knowledge sharing in a local context that is based on recognition of diversity in social patterns and embedding multiple forms and sources of knowledge. This conceptual paper contributes to the framing of justice principles with regards to local knowledge sharing and discusses practical implications for how different claims of justice by local actors can be addressed in sustainable tourism development.